Pengaruh Kepemimpinan Transformasional Terhadap Kinerja dan Keinginan Keluar Karyawan: Peran Komitmen Organisasional Sebagai Mediator - Lucky Tamengkel; Wehelmina Rumawas (Universitas Sam Ratulangi, 2022)
This study aims to examine the effect of transformational leadership on employee performance and intention to leave with organizational commitment as a mediator for hotel employees. The sample in this study were employees of five-star hotels in the city of Manado. Sampling used a non-probability convenience sampling technique. Questionnaires were used to collect data from 157 respondents. The data collected were analyzed using a structural equation model with the help of the SmartPLS software. The results of the study show that transformational leadership has a positive and significant effect on employee performance. Transformational leadership has a negative and insignificant effect on employees intention to leave. Transformational leadership has a positive and significant effect on employee organizational commitment. Employee performance has a negative and significant effect on employees intention to leave. Employee organizational commitment has a negative and significant effect on employees intention to leave. Organizational commitment has a positive and significant effect on employee performance.